Bone Morbidity and Recovery in Children With Acute Lymphoblastic Leukemia: Results of a Six‐Year Prospective Cohort Study. (22nd May 2018) - Ward, Leanne M; Ma, Jinhui; Lang, Bianca; Ho, Josephine; Alos, Nathalie; Matzinger, Mary Ann; Shenouda, Nazih; Lentle, Brian; Jaremko, Jacob L; Wilson, Beverly; Stephure, David; Stein, Robert; et al.
ABSTRACT: Osteoporotic fractures are a significant cause of morbidity in acute lymphoblastic leukemia (ALL). Our objective was to determine the incidence and predictors of fractures and recovery from osteoporosis in pediatric ALL over 6 years following glucocorticoid initiation. Vertebral fractures (VF) and vertebral body reshaping were assessed on annual spine radiographs, low‐trauma non‐VF were recorded at regular intervals and spine bone mineral density (BMD) was captured every 6 months for 4 years and then annually. A total of 186 children with ALL were enrolled (median age 5.3 years; range, 1.3 to 17.0 years). The cumulative fracture incidence was 32.5% for VF and 23.0% for non‐VF; 39.0% of children with VF were asymptomatic. No fractures occurred in the sixth year and 71.3% of incident fractures occurred in the first 2 years. Baseline VF, cumulative glucocorticoid dose, and baseline lumbar spine (LS) BMD Z ‐score predicted both VF and non‐VF. Vertebral body reshaping following VF was incomplete or absent in 22.7% of children. Those with residual vertebral deformity following VF were older compared to those without (median age 8.0 years at baseline [interquartile range IQR, 5.5 to 9.4] versus 4.8 years [IQR, 3.6 to 6.2], p = 0.04) and had more severe vertebral collapse (median maximum spinal deformity index 3.5 [IQR, 1.0 to 8.0] versus 0.5 [IQR, 0.0 to 1.0], p = 0.01). VF and low LS BMD Z ‐score at baseline as well as glucocorticoid exposure predicted incident VF and non‐VF. Nearly 25% of children had persistent vertebral deformity following VF, more frequent in older children, and in those with more severe collapse. These results suggest the need for trials addressing interventions in the first 2 years of chemotherapy, targeting older children and children with more severe vertebral collapse, because these children are at greatest risk for incident VF and subsequent residual vertebral deformity. © 2018 American Society for Bone and Mineral Research.